Corporate Social Responsibility In Consumer Behaviour Research: A Bibliometric–Systematic Review - Yeane Koyongian; Deske W. Mandagi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Corporate social responsibility (CSR) increasingly shapes consumer attitudes, relationships, and behavioural decisions, yet the literature remains fragmented across theories, methods, industries, and geographical contexts. This study conducts a bibliometric and systematic review of 506 journal articles to map the field’s development, identify publication and citation patterns, and examine its theoretical, methodological, and thematic structure. The findings reveal five interconnected research clusters: CSR-driven purchasing and responsible supply-chain decisions; CSR communication, consumer perceptions, and market responses; CSR-based brand relationships and customer outcomes; corporate reputation, trust, and CSR credibility; and consumer attitudes and emotional responses to responsible marketing. The field has evolved from an early emphasis on business ethics, philanthropy, stakeholder accountability, and corporate reputation toward more consumer-centred research on authenticity, motive attribution, trust, identification, loyalty, advocacy, willingness to pay, responsible consumption, avoidance, and boycotting behaviour. Based on these findings, the study proposes the Integrated CSR–Consumer Behaviour Framework, explaining how CSR practices and communication shape consumer perceptions of fit, authenticity, credibility, transparency, and corporate motives. These evaluations subsequently influence emotional, relational, and behavioural responses, subject to consumer, organisational, industry, cultural, and market conditions. The review consolidates fragmented knowledge and identifies directions for more theoretically integrated, context-sensitive, and methodologically diverse research.